Measuring energy security—An urban perspective - Yang, Jin; Chen, Bin (Journal of Environmental Accounting and Management, 2026)
Due to concurrent crises of energy and environment in urban areas, a systematic evaluation of urban energy security status is needed to construct a resource-saving and environmental-friendly society. This paper established an evaluation framework from the perspectives of energy supply, energy consumption, social-economic condition, environmental impact, and climate change. A modified grey relational analysis was also proposed to quantify the energy security degree of a city. The framework was then applied to Chongqing City to evaluate its energy security status during 2005—2010. Results showed that the security level of Chongqing kept increasing from 2005 to 2009. Due to the low energy security coefficient of the energy supply and climate change subsystem, a dramatic decline of energy security degree was observed in 2010. Finally, suggestions on the construction of secure energy system in Chongqing were put forward to shed light on policy making.